Metalloproteinase-7 (MMP-7) and their clinical relevance in urinary bladder cancer - Bakir, Wasan A. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Background: metalloproteinase-7 (MMP-7) is produced by stromal cells and by tumor cells,and overexpressed in a variety of epithelial and mesenchymal tumors. The aim of this study was to assessthe association of MMP-7 with clinical-pathological factors and to evaluate its diagnostic value in patients with bladdercarcinoma. Methods: Expression of MMP-7 was evaluated in tumor tissues of 32 urinary bladder cancer cases and 30 control groupswere fixed in formalin and embedded in paraffin blokes, then analyzedby in situ hybridization technique. Results: Expression of MMP-7was significantly higher in tumor compared to normal samples. The expression significantly associated with tumor grade and muscle invasion. Conclusion: MMP-7 may play an essential role in pathogenesis of bladder cancer. And may helpful to conventional diagnostic tools in malignancy as diagnosis.